1998
DOI: 10.1017/s000156600000012x
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Dysfunction and Specific Learning Disabilities in School-Aged Twins

Abstract: The frequency of the developmental dysfunction and specific learning disabilities were assessed in the retrospective study in the group of 56 school-aged twins. The relationships between genetic, perinatal and social factors and learning disability were also determined. It was found that 12.5% of twins had learning disabilities. The most common neurodevelopmental dysfunction were language disorders, poor graphomotor fluency and poor fine motor dexterity. It was also found that educational difficulty were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The case histories of Haverkamp et al showed an incidence of language disturbance in 13% of 94 twins [18], while our data, on a smaller sample, showed an incidence of 8.7%. An important phenomenon that could influence the language difficulties is the use of a secret language in the twin couple, already described [3]. The presence of secret language seems to be a developmental phenomenon occurring in the second year of life, with the emergence of immature speech.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The case histories of Haverkamp et al showed an incidence of language disturbance in 13% of 94 twins [18], while our data, on a smaller sample, showed an incidence of 8.7%. An important phenomenon that could influence the language difficulties is the use of a secret language in the twin couple, already described [3]. The presence of secret language seems to be a developmental phenomenon occurring in the second year of life, with the emergence of immature speech.…”
Section: Discussionmentioning
confidence: 97%
“…According to Pharoah[2], the incidence of cerebral palsy in term twins is 5-10 times higher than in singletons of the same gestational age whereas, for low gestational ages, there is the same incidence in the two groups of babies. In a prospective study from 1998 [3] regarding learning disorders in 28 school-aged twin pairs, it was shown that the commonest disturbances were writing and reading difficulties. In fact, 12.5% of twins had dyslexia and 10.7% dysgraphia, while about 20% had poor visual-motor coordination.…”
Section: Introductionmentioning
confidence: 99%